Räumliche Muster des demographischen Wandels in Europa: Geburtenrückgang und Verlängerung der Lebenserwartung - Gans, Paul; Schmitz-Veltin, Ansgar (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
At the beginning of the 21st century Europe is characterized by a negative natural population trend, which will even intensify in the next years. Countries with a comparatively positive trend face others with a strong decline of the number of inhabitants. On the regional level fertility and mortality levels differ substantially as well. Using the examples of France and Italy, the paper examines the spatial patterns of the decline of birth rates during the second demographic transformation as well as the rise of life expectancy since the 1970...s. In both countries a regional convergence of the total fertility rate (TFR) can be observed with a simultaneous divergence of selected indicators of generative behaviour. In addition, a converging trend may be detected for life expectancy. However, regions with migration gains register values rather above the average compared to those with migration losses. In regions where the decline of the birth rate began early, the future will bring strong phenomena of over-ageing. Altogether demographic conditions in the regions will differ increasingly.